Better Than Rational: A Naturalistic View of Economic Governance - J.W. Stoelhorst (Complexity, Governance & Networks, 2017)
The purpose of this paper is to present a recently emerging evolutionary approach to the study of human organization that I will refer to as ‘naturalistic’, and to highlight its integrative potential for the social and administrative sciences. This naturalistic approach considers the various forms of human cooperation as products of gene-culture co-evolutionary processes, and in doing so goes to the heart of the collective action problems that are central to explaining the human condition. Moreover, in building empirically grounded explanations of human behavior and organization, it also offers an alternative to the traditional view of governance in economic theory, with its emphasis on decentralized exchange and rational self-interested choice. The naturalistic approach both explains why human nature has evolved to the point where we often can do ‘better than rational’ in the face of the social dilemmas underlying collective action problems, and why modern forms of social, economic, and political organization are nevertheless always prone to being undermined by these same dilemmas.